2021
DOI: 10.3390/mi12101192
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Fluid Dynamic Study on Efficiency of a Wavy Microchannel/Heat Sink Containing Various Nanoparticles

Abstract: In this paper, a common and widely used micro-heat sink (H/S) was redesigned and simulated using computational fluid dynamics methods. This H/S has a large number of microchannels in which the walls are wavy (wavy microchannel heat sink: WMCHS). To improve cooling, two (Al2O3 and CuO) water-based nanofluids (NFs) were used as cooling fluids, and their performance was compared. For this purpose, studies were carried out at three Reynolds numbers (Re) of 500, 1000, and 1500 when the volume percent (φ) of the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Based on this result, it is clear and concise that silicon carbide nanofluid provides better heat transfer performance and this is mainly due to slightly higher thermal conductivity than another nanofluid. Khetib et al, have performed a numerical study to investigate the effect of addition of aluminium oxide and copper oxide nanoparticles in wavy MCHS [60]. The results showed that addition of nanoparticles have positive contribution to MCHS performance, compared to pure water.…”
Section: Nanoparticle Materialsmentioning
confidence: 99%
“…Based on this result, it is clear and concise that silicon carbide nanofluid provides better heat transfer performance and this is mainly due to slightly higher thermal conductivity than another nanofluid. Khetib et al, have performed a numerical study to investigate the effect of addition of aluminium oxide and copper oxide nanoparticles in wavy MCHS [60]. The results showed that addition of nanoparticles have positive contribution to MCHS performance, compared to pure water.…”
Section: Nanoparticle Materialsmentioning
confidence: 99%
“…Using performance improvement approaches, the PCM’s phase transition rate, thermal conductivity, latent heat storage capacity, and thermo-physical stability are all enhanced. On the other hand, nanofluids are well known for their ability to enhance heat transfer rates [ 25 , 26 , 27 , 28 ]. However, unlike PCM, nanofluids are not able to restore or release heat.…”
Section: Introductionmentioning
confidence: 99%